2013
DOI: 10.1007/s00776-012-0327-4
|View full text |Cite
|
Sign up to set email alerts
|

Over 10-year follow-up of functional outcome in patients with bone tumors reconstructed using distraction osteogenesis

Abstract: Background The aim of this study was to investigate the long-term functional capabilities of patients who underwent bone distraction for the treatment of bone defects caused by bone tumor excision.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
49
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 58 publications
(59 citation statements)
references
References 34 publications
1
49
0
2
Order By: Relevance
“…21,28-31 Distraction osteogenesis with external fixation is also an established form of treatment but carries risks of increased time of treatment and pin-or wire-tract infections. 32,33 VFGs will remodel, hypertrophy, and unite to host bone in response to mechanical stresses, providing a biological reconstruction more resistant to infection, chemotherapy and radiotherapy, with low rates of late complications. [10][11][12][13][14] However, previous studies were limited by small numbers of patients, consequently subgroup analysis of patient and surgical parameters was difficult.…”
Section: Discussionmentioning
confidence: 99%
“…21,28-31 Distraction osteogenesis with external fixation is also an established form of treatment but carries risks of increased time of treatment and pin-or wire-tract infections. 32,33 VFGs will remodel, hypertrophy, and unite to host bone in response to mechanical stresses, providing a biological reconstruction more resistant to infection, chemotherapy and radiotherapy, with low rates of late complications. [10][11][12][13][14] However, previous studies were limited by small numbers of patients, consequently subgroup analysis of patient and surgical parameters was difficult.…”
Section: Discussionmentioning
confidence: 99%
“…[17][18][19][20] As such, the studies described herein provide important new information regarding potential clinical applications. 20 Based on previous studies, we observed that exposure to chemotherapy can occur preoperatively, postoperatively, and even simultaneously with bone repair/regeneration. 21 Therefore, to develop and standardize a mouse model for CDP toxicity we chose to perform the DO surgery simultaneously with the first of five daily CDP injections.…”
mentioning
confidence: 90%
“…During DO, bone formation process spatially well organized and temporally distinct from resorptive processes induced later. In addition, recent literature suggests that DO is emerging as an appropriate protocol for osteosarcoma patients and does provide significant benefit to to patients compared with other critical size defect repair procedures 17-20 . As such, the studies described herein provide important new information regarding potential clinical applications 20 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Functional outcome would be better overtime. Watanabe et al reported functional score improved within 2 years after extremity tumor surgery and maintained after that [12]. Our cases are average 5 years follow-up and the functional score should be stabilized in most of the cases.…”
Section: Resultsmentioning
confidence: 51%